Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM di KPP Pratama Badung Selatan - Sherley Diana Thandung; Ni Luh Wayan Sayang Telagawathi; Komang Endrawan Sumadi Putra (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyse the effect of taxpayer awareness, tax knowledge, and tax sanctions on the compliance of Micro, Small, and Medium Enterprises (MSMEs) taxpayers at KPP Pratama Badung Selatan. The background of this study is based on the relatively low level of MSME taxpayer compliance, as reflected in the low rate of annual tax return (SPT) reporting compared to the number of registered taxpayers. This study employs a quantitative approach with a causal-comparative research design. The population consists of all MSME taxpayers registered at KPP Pratama Badung Selatan, totalling 11,521 taxpayers, with a sample of 100 respondents selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analysed using multiple linear regression with the assistance of SPSS. Prior to hypothesis testing, classical assumption tests were conducted, including normality, multicollinearity, and heteroscedasticity tests. The results indicate that taxpayer awareness, tax knowledge, and tax sanctions have a positive and significant effect on MSME taxpayer compliance, both partially and simultaneously. These findings suggest that improving taxpayer awareness and tax knowledge, along with the consistent and firm enforcement of tax sanctions, can enhance MSME taxpayer compliance. This study is expected to contribute to the Directorate General of Taxes in formulating more effective strategies to improve taxpayer compliance, particularly in the MSME sector.